Invasive Acacia mangium Leaf Litter Modifies Soil Chemical Properties of A Bornean Tropical Heath Forest: A Soil Incubation Study - Mohamad Hilmi Ibrahim,; Faizah Metali,; Kushan U Tennakoon,; Rahayu Sukmaria Sukri, (Tropical Life Sciences Research, 2025)
This study investigated the effects of Acacia mangium Willd. leaf litter on soil chemical properties of a tropical heath forest in Borneo using a controlled soil incubation experiment. The litter of exotic A. mangium and selected native heath forest species (Buchanania arborescens Blume., Calophyllum inophyllum L., Dillenia suffruticosa Griff. and Ploiarium alternifolium Vahl.) were incubated with heath forest soils collected under natural conditions and nine different treatments of heath forest soils (soils without leaf litter, soils treated with single species leaf litter, and soils treated with native leaf litter with and without A. mangium leaf litter). We quantified mass litter loss (%), and soil concentrations of exchangeable nitrogen (NO3? and NH4+) and cations (K+, Ca2+ and Mg2+), available phosphorus (P), total organic carbon (TOC) and organic matter (OM), and total acidity with exchangeable concentrations of Al3+ and H+ in each treatment after a 9-month incubation period. Mass litter loss (%) varied significantly between species, with A. mangium leaf litter only showing higher mass loss than D. suffruticosa litter, but lower than C. inophyllum litter. The effects of incubation with single-species native leaf litter were variable and species-specific, but incubation with A. mangium litter increased soil pH and exchangeable NO3? and K+ concentrations and decreased exchangeable Al3+ concentrations. Soils incubated with a combination of C. inophyllum and A. mangium leaf litters, as opposed to those incubated with C. inophyllum alone, exhibited decreased pH, lower total organic carbon (TOC), and reduced exchangeable concentrations of potassium (K+) and magnesium (Mg2+). Additionally, there was an increase in organic matter (OM) content, total acidity, and exchangeable concentrations of ammonium (NH4+) and hydrogen (H+). Our results provide preliminary evidence that C. inophyllum may be a promising native plant species for use in enrichment planting of degraded or disturbed tropical heath forests with co-occurring invasive A. mangium.